Tracking the SDGs in an ‘integrated’ manner: A proposal for a new index to capture synergies and trade-offs between and within goals - Biggeri, Mario; Clark, David A.; Ferrannini, Andrea; Mauro, Vincenzo (World development, 2019)
•Agenda 2030 requires tracking progress towards the SDGs in an ‘integrated’ way.•The SDG Index does not allow for the ‘integrated’ nature of the SDGs.•The MSI overcomes problems associated with the arithmetic and geometric means.•The new MSI inspired I-SDI embraces synergies between and within goals.•The I-SDI provide new monitoring tools for global, national and local policy. Monitoring the Sustainable Development Goals (SDGs) is an important challenge and strategic opportunity for stakeholders and beneficiaries involved with Agenda 2030 at all levels. To monitor progress across a diverse set of goals with multiple targets and indicators and to track overall progress, Jeffrey Sachs and associates have developed the SDG Index. Although their index is robust and permits comparisons across countries, it neglects the ‘balanced’ and ‘integrated’ nature of the SDGs (set out in Transforming Our World), and exhibits well-known problems associated with the use of an arithmetic mean (which assumes perfect substitution between dimensions). To overcome these difficulties, this paper introduces an adjusted ‘Integrated Sustainable Development Index’ (I-SDI) that can take account of trade-offs and synergies between goals and targets as well as across the economic, social and environmental spheres of sustainable development. This is accomplished by introducing a new aggregation method based on the Multidimensional Synthesis of Indicators (MSI) approach. This approach overcomes well-known problems associated with replacing the arithmetic mean with the geometric mean (a difficulty encountered by the post-2010 HDI). Specifically, it makes an allowance for the heterogeneity of dimensions, while avoiding the tendency of the geometric mean to collapse to zero. In this paper, the I-SDI scores and rankings are compared with those generated by the SDG Index and the geometric mean. Moreover, to capture the heterogeneity within goals, the I-SDI2 is introduced (which applies the MSI method within as well as between goals). By taking account of heterogeneity within and between goals as well as across the economic, social and environmental dimensions of sustainable development, and by capturing synergies and trade-offs among indicators, our study reveals crucial differences in I-SDI scores and rankings that illustrate the value of a more flexible and integrated measure for guiding policymakers and monitor overall progress.